Characterization of an Isolate That Uses Vinyl Chloride as a Growth Substrate under Aerobic Conditions - Verce, Matthew F. (American Society for Microbiology, 2000)
An aerobic enrichment culture was developed by using vinyl chloride (VC) as the sole organic carbon and electron donor source. VC concentrations as high as 7.3 mM were biodegraded without apparent inhibition. VC use did not occur when nitrate was provided as the electron acceptor. A gram-negative, rod-shaped, motile isolate was obtained from the enrichment culture and identified based on biochemical characteristics and the sequence of its 16S rRNA gene as Pseudomonas aeruginosa, designated strain MF1. The observed yield of MF1 when it was grown on VC was 0.20 mg of total suspended solids (TSS)/mg of VC. Ethene, acetate, glyoxylate, and glycolate also served as growth substrates, while ethane, chloroacetate, glycolaldehyde, and phenol did not. Stoichiometric release of chloride and minimal accumulation of soluble metabolites following VC consumption indicated that the predominant fate for VC is mineralization and incorporation into cell material. MF1 resumed consumption of VC after at least 24 days when none was provided, unlike various mycobacteria that lost their VC-degrading ability after brief periods in the absence of VC. When deprived of oxygen for 2.5 days, MF1 did not regain the ability to grow on VC, and a portion of the VC was transformed into VC-epoxide. Acetylene inhibited VC consumption by MF1, suggesting the involvement of a monooxygenase in the initial step of VC metabolism. The maximum specific VC utilization rate for MF1 was 0.41 μmol of VC/mg of TSS/day, the maximum specific growth rate was 0.0048/day, and the Monod half-saturation coefficient was 0.26 μM. A higher yield and faster kinetics occurred when MF1 grew on ethene. When grown on ethene, MF1 was able to switch to VC as a substrate without a lag. It therefore appears feasible to grow MF1 on a nontoxic substrate and then apply it to environments that do not exhibit a capacity for aerobic biodegradation of VC.